1956
DOI: 10.1063/1.1722220
|View full text |Cite
|
Sign up to set email alerts
|

Slippage of Water over Nonwettable Surfaces

Abstract: When water flows over glass which has been treated with the vapor of dimethyldichlorosilane and thus made water repellent, slipping on the boundary between the solid surface and the water takes place. This is is shown in capillary tubes of various diameters. The amount of slipping is small, but measurable. It disappears or becomes extremely small in case of turbulent flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(113 citation statements)
references
References 3 publications
4
104
0
2
Order By: Relevance
“…The conclusions have been confirmed by Molecular Dynamics simulations [135] and are consistent with studies of flow in capillaries with diameters of tens of nanometers [3,91]. In this context, the large number of recent published experiments reporting some form of (apparent) slip with λ ∼ 1 nm−1 µm in the flow of Newtonian liquids is surprising [9,16,17,18,29,30,32,33,38,39,40,67,87,88,68,108,116,125,126,150,162,163,178,192,193,194,195], and has allowed to re-discover a few early [29] Poly(carbonate)+PVP SDS solutions studies reporting some degree of slip [21,34,46,141,160]. In part, this chapter is an attempt to describe and interpret these more recent experimental results.…”
Section: Newtonian Liquids: No-slip? Slip?supporting
confidence: 79%
“…The conclusions have been confirmed by Molecular Dynamics simulations [135] and are consistent with studies of flow in capillaries with diameters of tens of nanometers [3,91]. In this context, the large number of recent published experiments reporting some form of (apparent) slip with λ ∼ 1 nm−1 µm in the flow of Newtonian liquids is surprising [9,16,17,18,29,30,32,33,38,39,40,67,87,88,68,108,116,125,126,150,162,163,178,192,193,194,195], and has allowed to re-discover a few early [29] Poly(carbonate)+PVP SDS solutions studies reporting some degree of slip [21,34,46,141,160]. In part, this chapter is an attempt to describe and interpret these more recent experimental results.…”
Section: Newtonian Liquids: No-slip? Slip?supporting
confidence: 79%
“…The physical parameters (i.e., slip length, surface tension, contact angle, and density) used in the simulation are listed in Table 2. a The range of slip length, which is the interactions between fluids and solid surfaces, is based on literature data (Schnell, 1956;Churaev et al, 1984;Watanabe et al, 1999;Baudry et al, 2001;Craig et al, 2001;Tretheway and Meinhart, 2002;Cheng and Giordano, 2002;Jin et al, 2004;Joseph and Tabeling, 2005;Neto et al, 2005;Choi and Kim, 2006;Joly et al, 2006;Zhu et al, 2012;Li et al, 2014). b The lower limits of the surface tension of toluene-derived SOM were determined as 28 mN m −1 , the surface tension of liquid toluene at 293 K (Adamson and Gast, 1997).…”
Section: Poke-flow Technique In Conjunction With Fluid Simulationsmentioning
confidence: 99%
“…A number of new studies have confirmed the existence of a liquid slip over certain solid surfaces, as summarized in recent reviews. [5][6][7] Although a few studies 8,9 have reported a slip over hydrophilic surfaces, many theoretical, 10,11 experimental, [12][13][14][15][16][17][18][19][20][21][22][23] and numerical 24 studies have reported that hydrophobic surfaces allow a noticeable slip ranging from nanometers to a micron in "slip length" ͑the linearly extrapolated distance into a solid surface at which a no-slip condition would hold true͒. Several reasons have been proposed for the slip over hydrophobic surfaces, including a molecular slip, 10 a decrease in the viscosity of the boundary layer, 11 the small dipole moment of a polar liquid, 23 and a gas gap or nanobubbles at the liquid-surface interface.…”
Section: Introductionmentioning
confidence: 99%